2015
DOI: 10.1177/0020731415611634
|View full text |Cite
|
Sign up to set email alerts
|

Why is There so Much Controversy Regarding the Population Health Impact of the Great Recession? Reflections on Three Case Studies

Abstract: In the aftermath of the Great Recession, public health scholars have grown increasingly interested in studying the health consequences of macroeconomic change. Reflecting existing debates on the nature of this relationship, research on the effects of the recent economic crisis has sparked considerable controversy. On the one hand there is evidence to support the notion that macroeconomic downturns are associated with positive health outcomes. On the other hand, a growing number of studies warn that the current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
1
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 118 publications
(166 reference statements)
2
31
1
3
Order By: Relevance
“…Despite earlier reports of increasing homicides9, and all-cause mortality11, our comparison with pre-crisis trends revealed no evidence of changing trends during the crisis, which is in line with mortality trends observed during recessions in the past15. Close monitoring is required in order to explore whether the increase observed in 2015 signifies a dramatic change in the course of the Greek crisis or it was a statistical anomaly without further implications.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…Despite earlier reports of increasing homicides9, and all-cause mortality11, our comparison with pre-crisis trends revealed no evidence of changing trends during the crisis, which is in line with mortality trends observed during recessions in the past15. Close monitoring is required in order to explore whether the increase observed in 2015 signifies a dramatic change in the course of the Greek crisis or it was a statistical anomaly without further implications.…”
Section: Discussioncontrasting
confidence: 51%
“…One issue that has already been highlighted as a negative consequence of the economic crisis is the increase in suicides and suicide attempts1516. Our analysis showed that the standardised mortality from suicides increased rapidly after 2009.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…In the Greek population, early reports have suggested a negative effect of financial crisis on public health [3, [9][10][11][12], and remarkably on respiratory health [1, 9,10,[13][14][15]. The impact of the Greek downturn on respiratory health was apparent even though most studies used data covering only the first years of the crisis and reported its short-term effects [16]. This article summarises the overall impact of the financial crisis on chronic obstructive pulmonary disease (COPD) burden throughout the period of economic downturn, analysing the case study of Greece.…”
Section: Introductionmentioning
confidence: 99%
“…One key point of much of this work is that the institutional context in which economic disruptions occur may modify any impact on suicide rates [48]. For example, it has been argued that the impact of recessions is weaker or not evident in places with stronger labor market protections, such as Scandinavia [7,49].…”
Section: Discussionmentioning
confidence: 99%